2005
DOI: 10.1063/1.1989727
|View full text |Cite
|
Sign up to set email alerts
|

Fast growing double tearing modes in a tokamak plasma

Abstract: Configurations with nearby multiple resonant surfaces have broad spectra of linearly unstable coupled tearing modes with dominant high poloidal mode numbers m. This was recently shown for the case of multiple q = 1 resonances [Bierwage et al., Phys. Rev. Lett. 94 (6), 65001 (2005)]. In the present work, similar behavior is found for double tearing modes (DTM) on resonant surfaces with q >= 1. A detailed analysis of linear instability characteristics of DTMs with various mode numbers m is performed using numeri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(103 citation statements)
references
References 43 publications
8
95
0
Order By: Relevance
“…The purpose of the present paper is (i) to shown that the findings of Ref. [4] agree with linear DTM theory, and (ii) to present first nonlinear simulation results involving high-m DTMs for cases with q s = 1 and q s > 1. For simplicity, a reduced magnetohydrodynamic (RMHD) model is employed.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…The purpose of the present paper is (i) to shown that the findings of Ref. [4] agree with linear DTM theory, and (ii) to present first nonlinear simulation results involving high-m DTMs for cases with q s = 1 and q s > 1. For simplicity, a reduced magnetohydrodynamic (RMHD) model is employed.…”
Section: Introductionmentioning
confidence: 75%
“…Despite the lack of a distinguished band of weakly coupled modes in the cases considered here, we conjecture that an estimate for the mode number of the fastest growing mode m peak may be obtained from the transition criterion in Eq. [4]), which suggests that m peak ≈ m trans + 1. Tests with other configurations gave similarly good agreement, despite the fact that the x s dependence is described only approximately under the assumption that q(r) is parabolic around r = r 0 .…”
Section: Comparison With Linear Theorymentioning
confidence: 94%
See 3 more Smart Citations